A Hierarchical Linear Models Approach to Explaining Reflective Thinking Skill Through Problem Solving - Gürol Zırhlıoğlu; Osman Tat (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The purpose of this study is to identify the student and teacher level factors that explain the reflective thinking skills through problem solving of elementary school pupils. The research was conducted in public elementary schools in three Van districts: Pekyolu, Tuşba, and Edremit. The study's sample consists of 52 mathematics teachers and 1126 elementary school pupils. "Participant Information Form," "Reflective Thinking Ability Through Problem Solving Scale," and "Mathematics Problem Solving Attitude Scale" are data gathering tools for pupils. Teachers' data was gathered using the "Participant Information Form," the "Reflective Thinking Tendency Scale for Teachers and Preservice Teachers," and the "Scale for Learner Autonomy Support."According to the results, it is found that the 90 % of variance in dependent variable can be explained by student level variables. Teacher level variables could explain 10% of outcome variance. The gender of students, receiving private tuition, book reading frequency, time devoted to studying mathematics, and attitude through problem solving are significant factors that can predict the dependent variable. Moreover, students' reflective thinking ability can be significantly influenced by teacher-level factors, such as teachers' knowledge of problem-solving steps and their tendency for reflective thinking. The authors recommend education or seminars that develop teachers’ reflective thinking tendency and problem-solving courses be provided in mathematics teaching undergraduate programs. Students should be supported in gaining reading habit and activities that have positive impact on the students’ problem-solving attitude.